Genetic Diversity, Community Assembly, and Shaping Factors of Benthic Microbial Eukaryotes in Dongshan Bay, Southeast China - Gu, Rong; Sun, Ping; Wang, Ying; Yu, Fengling; Jiao, Nianzhi; Xu, Dapeng (Frontiers in Microbiology, 2020)
Microbial eukaryotes are pivotal components of marine ecosystems. However, compared with the pelagic environments, the diversity distribution and the driving mechanisms of microbial eukaryotes in the marine sediments have rarely been explored. In this study, sediment cores were collected along a transect from inner to outer Dongshan Bay, southeast China. By combining high throughput sequencing of SSU rRNA gene with measurements on multiple environmental variables, the genetic diversity, community structure and assembly processes, and environmental shaping factors were investigated. Alveolata (mainly Ciliophora and Dinophyceae), Rhizaria (mainly Cercozoa), and Stramenopiles (mainly Bacillariophyta) were the most dominant groups in terms of both relative sequence abundance and OTU richness. Grain size composition of the sediment was the primary factor determining the alpha diversity of microbial eukaryotes followed by sediment depth and heavy metal, including Cr, Zn, and Pb. Geographic distance and water depth surpassed other environmental factors to be the primary factors shaping the microbial eukaryotic communities. Dispersal limitation was the primary driver of the microbial eukaryotic communities, followed by drift and homogeneous selection. Overall, our study shed new light on the spatial distribution patterns and controlling factors of benthic microbial eukaryotes in a subtropical bay which is subject to increasing anthropogenic pressure.